Exploring the Circumstellar Environment of Tycho’s Supernova Remnant. II. Impact on the Broadband Nonthermal Emission - Ryosuke Kobashi; Shiu-Hang Lee; Takaaki Tanaka; Keiichi Maeda (The Astrophysical Journal)
While the environment around Tycho's supernova remnant has long been believed to be close to homogeneous, the latest analysis of Chandra data has identified a substantial deceleration of the forward shock, which poses a major challenge to this picture. R. Kobashi et al. showed that the existence of dense molecular cloud (MC) surrounding a rarefied wind-like circumstellar matter (CSM) can explain this observational finding in terms of the shock-expansion dynamics, supporting the so-called single-degenerate scenario for the progenitor system. We here extend this work to study the nonthermal emission processes and investigate whether such an environment is consistent with the observed multiwavelength spectrum. While the simulated broadband spectrum based on the wind–MC environment is largely consistent with observations, we find that such an environment predicts a harder gamma-ray spectrum than observed due to the relatively low CSM density in the cavity interior of the MC. This difference can be at least partially attributed to the present 1D setup of the model, which does not account for the clumpy and multidimensional structure of the CSM. Our model provides predictions for the long-term evolution of the broadband spectrum, which can be used to further probe Tycho's surrounding environment in the future, a key to resolving the long-standing issue of Type Ia supernova progenitor channels.